Titanium isotopes and the radial heterogeneity of the solar system - Leya, I; Schoenbaechler, M; Wiechert, U; Kraehenbuehl, U; Halliday, A (2008)
The solar system is assumed to be uniform on a large scale in terms of the isotope composition of refractory elements. Here we show that the titanium (Ti) isotope compositions of carbonaceous chondrites differ from those of ordinary chondrites, eucrites, mesosiderites, ureilites, the Earth, Moon, and Mars, all of which are indistinguishable. Leachates and mineral separates demonstrate that this feature is homogeneously distributed within a range of phases in the carbonaceous chondrites Allende and Renazzo. The data therefore indicate that the solar nebula that fed planetesimals between ∼ 1 AU and ∼ 2.4 AU, e.g. Earth, Moon, Mars and the parent bodies of ordinary chondrites, eucrites, ureilites, and mesosiderites, was homogeneous for Ti (and Sr, Ba, Nd, Sm) isotopes. In contrast, carbonaceous chondrites, which probably formed beyond ∼ 2.7 AU appear to have acquired a distinct mix of primitive components, which is consistent with their lack of depletion in volatile elements and late formation. © 2007 Elsevier B.V. All rights reserved.